2015
DOI: 10.1155/2015/858015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Features for Movement Prediction from Single-Trial Movement-Related Cortical Potentials in Healthy Subjects and Stroke Patients

Abstract: Detection of movement intention from the movement-related cortical potential (MRCP) derived from the electroencephalogram (EEG) signals has shown to be important in combination with assistive devices for effective neurofeedback in rehabilitation. In this study, we compare time and frequency domain features to detect movement intention from EEG signals prior to movement execution. Data were recoded from 24 able-bodied subjects, 12 performing real movements, and 12 performing imaginary movements. Furthermore, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Each group of features was considered in a ten-fold test procedure to design a linear discriminant analysis (LDA) 1 classifier [see details in (Kamavuako et al, 2015)]. In this method nine folds were used for the validation step to 2 obtain the best LDA classifier and one remaining fold was applied to test the classifier.…”
Section: Classification Procedures 20mentioning
confidence: 99%
“…Each group of features was considered in a ten-fold test procedure to design a linear discriminant analysis (LDA) 1 classifier [see details in (Kamavuako et al, 2015)]. In this method nine folds were used for the validation step to 2 obtain the best LDA classifier and one remaining fold was applied to test the classifier.…”
Section: Classification Procedures 20mentioning
confidence: 99%
“…Although it has been shown that patients that suffer from, e.g., stroke, are feasible to perform movement-imagination despite chronic or severe motor impairments [ 68 , 69 , 164 ], different kinds of brain damages can affect the EEG [ 165 , 166 , 167 , 168 , 169 , 170 ] and EMG [ 171 , 172 ], and hence, possibly the performance of the proposed system. However, MRCP-based BCIs can be successfully used by patients suffering from stroke [ 173 , 174 , 175 ]. For other neurological diseases, such as amyotrophic lateral sclerosis, it has been shown that certain MRCP characteristics do not differ from healthy patients [ 176 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different from most classifiers (Bai et al, 2007;Bhagat, 2014;Jiang et al, 2015;Kamavuako et al, 2015;Lew et al, 2012;2014;Nikulin et al, 2008), the detector does not need training data to determine its parameters. The only previous knowledge needed for the SFT detector is the electrophysiological response, i.e., the only characteristic needed is the desynchronization present as a persistent feature related to movement intention, which is used to detect whether the volunteer intended a movement or not.…”
Section: Discussionmentioning
confidence: 99%
“…Volume 31, Number 4, p. 285-294, 2015 Usually, the detection of movement intention is performed using classifiers that are parameterized, validated and tested in order to obtain the classification accuracy (Bai et al, 2007). In BMI, the most commonly used classifiers include linear discriminant analysis (Kamavuako et al, 2015;Lew et al, 2012;2014), matched filters (Jiang et al, 2015), support vector machines (Bhagat, 2014), common spatial patterns (Nikulin et al, 2008) multivariate linear classifiers (Bai et al, 2011), among others. For successful classification, it is required to have a training record available in order to determine the working parameters of the classifier.…”
Section: Introductionmentioning
confidence: 99%